Effect of Mean Flow on the Transmission Loss of a Doubly Tuned Flow Reversal Muffler - Chetan Dayanand Gaonkar; Thappaganadoddi Nagabushnasharma Sreenivasa (Advances in Technology Innovation, 2024)
The same-end-inlet-outlet (SEIO) muffler, also referred to as a flow reversal muffler under flow conditions, features inlet and outlet pipes positioned on the same side of the chamber. Recently, a parametric expression has been developed to determine the end correction for double tuning of the SEIO muffler. This study extends the development of the SEIO muffler by experimentally validating the derived end correction expressions. Additionally, the tuning of the muffler is assessed with a mean flow using 3-D computational fluid dynamics, solving the linearized Navier-Stokes equation. This investigation explores the impact of flow conditions (Mach number 0.05 and 0.1) and temperature conditions (T = 733 K and 953 K) on the transmission loss (TL) of a doubly tuned muffler. The findings reveal that the muffler maintains its double tuning, even in the presence of mean flow at elevated temperatures, albeit with somewhat of a reduction in performance.